(-7x+1)-(-6x-5)=1

Simple and best practice solution for (-7x+1)-(-6x-5)=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-7x+1)-(-6x-5)=1 equation:


Simplifying
(-7x + 1) + -1(-6x + -5) = 1

Reorder the terms:
(1 + -7x) + -1(-6x + -5) = 1

Remove parenthesis around (1 + -7x)
1 + -7x + -1(-6x + -5) = 1

Reorder the terms:
1 + -7x + -1(-5 + -6x) = 1
1 + -7x + (-5 * -1 + -6x * -1) = 1
1 + -7x + (5 + 6x) = 1

Reorder the terms:
1 + 5 + -7x + 6x = 1

Combine like terms: 1 + 5 = 6
6 + -7x + 6x = 1

Combine like terms: -7x + 6x = -1x
6 + -1x = 1

Solving
6 + -1x = 1

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + -1x = 1 + -6

Combine like terms: 6 + -6 = 0
0 + -1x = 1 + -6
-1x = 1 + -6

Combine like terms: 1 + -6 = -5
-1x = -5

Divide each side by '-1'.
x = 5

Simplifying
x = 5

See similar equations:

| 8cos(8x)=0 | | -(7x+1)-(-6y-5)=1 | | 3x+27y=54 | | 3(x^2+20)=18 | | 3+15x-2=8x+105-6x | | 5x^2+17x+5=0 | | x/81=38 | | 5y+4y+7y-8= | | x/56=90 | | 4x=18/2x | | 2x^2+11+15=0 | | x/8=-28 | | 8x^2-82=-10 | | 4(-x+5)=11[5(4x-2)] | | 5x+45=122 | | -10.9x=76.3 | | x(x-7)=x-19 | | -3m-8=-14 | | x^2+52=12x | | x^2+4x-6= | | 24b^2-4b-8=0 | | m*8+2=4 | | -3p=21 | | 5(g-4)-3g-2=8(g+1) | | 2.7x-3.2-2.3x=-0.6x-5.6 | | 2x-x^2-5x-25=0 | | 0.89x=289.25 | | -13(v-6)=-5+2(5v+12) | | 45x^2+61x+20=0 | | 2x-x-9x= | | 22-46=4(x-2)-4 | | a-b+2=c |

Equations solver categories